Results of native and transplant kidney biopsies of children in a single center over a 15 years period. (1st January 2017) - Isiyel, Emel; Fidan, Kibriya; Buyukkaragoz, Bahar; Akcaboy, Meltem; Kandur, Yasar; Gonul, Ipek Isik; Buyan, Necla; Bakkaloglu, Sevcan; Soylemezoglu, Oguz
Abstract: Renal biopsy is an important diagnostic procedure in pediatric nephrology. This study retrospectively investigates the indications, results and complications in a single tertiary children's hospital in Turkey. We evaluated the native and transplant kidney biopsies in Gazi University Pediatric Nephrology Department between 2001 and 2015. A total of 196 biopsies (144 natives and 52 transplants) were included into the study. The mean age of the patients was respectively 10.8 ± 3.5, 13.9 ± 1.5 years. The main indication for a biopsy was non-nephrotic proteinuria with or without hematuria ( n = 35), followed by steroid-resistance nephrotic syndrome (SRNS) ( n = 34) and Henoch-Schönlein purpura (HSP)–related proteinuria ( n = 20) for native kidneys. We found that focal segmental glomerulosclerosis (FSGS) (11.7%) was the most common histopathologic diagnosis for native kidneys, but acute cellular rejection (7.6%) was the most common histopathologic diagnosis for transplant kidneys. The complication rate in our study was founded 6.6% totally. Different complication rates were found in other studies; however, we think that this difference comes from the inspecting methodology of the complications. Hence, we wanted to share our own experience in the context of other studies in the literature.